Palliative care strategies in the management of people with serious cases of COVID-19 - Eleandro do Prado; Camila Wohlenberg Camparoto; Angelica Yukari Takemoto; Sueli Mutsumi Tsukuda Ichisato; Maria Emília Grasso Busto Miguel; Sonia Silva Marcon (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze the assistance strategies in palliative care developed in the COVID-19 pandemic for critically ill patients and their families. Methods: an integrative review carried out in August 2021 and updated in April 2022 in the Base de Dados de Enfermagem (BDENF), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medical Literature Analysis and Retrieval System Online (MEDLINE), US National Library of Medicine (PubMed), Web of Science databases, and presented in the PRISMA flowchart. Results: thirteen works were selected for reading and content analysis, from which emerged the two main themes that reflect the reality evidenced in this context: The sudden advent of COVID-19 with impacts on palliative care; and The strategies used in palliative care to mitigate these impacts. Final Considerations: palliative care is the best strategy for providing health care, used as a comfort to bring relief and comfort to patients and families.